Effects of equaling either concentrate and nutrient intake on milk production of dairy buffaloes: a meta-analysis - Afiqah A. Samad, Fadzlin; Faiz Mohd Azmi, Amirul; Affan Ab Azid, Muhamad; Mu’izz Zalazilah, Hafizin; Zulkifli, Syakirah; Edriana Mohd Jasmi, Izreen; Baqir Irfani Rahimin Affand, Muhammad; Zamri Saad, Mohd; Zuki Abu Bakar, Md; Irawan, Agung; Norma Respati, Adib; Jayanegara, Anuraga; et al. (ResearchersLinks, 2023)
This study presents a meta-analysis of 20 independent studies to investigate the relationship between forage to concentrate (FC) ratio, nutrient constituent, and nutrient intake on milk production and milk component in dairy buffalo. A dataset comprised of 89 comparisons from multi-species of buffaloes were analyzed according to a linear mixed model methodology with explanatory variables declared as fixed effects and individual study as random effects. The results showed a negative curvilinear pattern of milk yield across buffaloes breeds in response to the increasing FC ratio (P<0.05; R2 = 0.828) and strong linear increased in response to the increasing DMI (P<0.01; R2 = 0.841). The interaction effect was found between breed of buffaloes and NDF content of the diets (P = 0.028) and between breeds with FC ratio (P = 0.016) whereas increasing NDF content linearly decreased milk fat of Murrah buffalo (P<0.05; R2 = 0.90) but did not affect other species. A decreasing trend was also noticed on the milk protein content of Murrah buffalo in association with increasing FC ratio (P<0.05; R2 = 0.76). In addition, increasing NFC content in the diets also contributed to decrease milk protein content across the breed of buffaloes but without a strong correlation (P<0.05; R2 = 0.149). For milk lactose content, CP intake was the only factor explaining the decreased trend when the level increased (P<0.05). To conclude, DMI and FC ratio are two predictor variables with the greatest effect on milk yield of inter-species lactating dairy buffaloes, noticeably an importance role of concentrate supplementation for buffaloes to increase milk production. Milk fat and milk protein contents were influenced by NDF content of the diets, dependently varied among species.